Development of Electronic Student Worksheets with a Scientific Approach to Static Fluids Material to Improve Critical Thinking Skills of SMAN 9 Merangin Students - Nurtanti Yutia; Yusnaidar; M. Haris Effendi Hasibuan (Postgraduate, University of Mataram, 2023)
Teaching materials in their role as providers of information are really needed by educators and student. The purpose of this research is to develop teaching materials in the form of e-LKPD with a scientific approach to static fluid material to improve critical thinking skills at SMAN 9 Merangin which can be used in the learning process. This development research uses a 4D development model. The test subjects consisted of a small group consisting of 10 people and a large group consisting of 30 people who were students of SMAN 9 Merangin. The instruments used in this research were interviews, questionnaires, pretest-posttest questions, and validation assessment sheets. The data analysis technique used in this research is descriptive research with a quantitative approach. The validation results from material and media experts show that the teaching materials developed are very valid for small group trials. Teacher assessments and student responses to the media are very good. The effectiveness of e-LKPD teaching materials in improving critical thinking skills was carried out by a Paired Sample T-Test with the decision that the hypothesis was accepted and a large group test was carried out to obtain a fairly effective level of effectiveness with an average value of 0.6187 or 61.8696%. It can be concluded that the development of e-LKPD teaching materials with a scientific approach to static fluid material to improve critical thinking skills is feasible and effective for use in the learning process. 6187 or 61.8696%. It can be concluded that the development of e-LKPD teaching materials with a scientific approach to static fluid material to improve critical thinking skills is feasible and effective in the learning process. 6187 or 61.8696%. It can be concluded that the development of e-LKPD teaching materials with a scientific approach to static fluid material to improve critical thinking skills is feasible and effective for use in the learning process.